Analisis Indeks Risiko Lingkungsn Tempat Pemrosesan Akhir (TPA) Sampah Mojorejo Di Kabupaten Sukoharjo, Provinsi Jawa Tengah - Afifah Asri Larasati; Andi Sungkowo; Farida Afriani Astuti (Jurusan Teknik Lingkungan, FTM, Universitas Pembangunan Nasional “Veteran” Yogyakarta, 2019)
Mojorejo landfill establised since 1994 and already operating more than five years with open dumping operating system. Based on Undang-Undang Republik Indonesia No 18 Tahun 2008, the landfill sould not be operated again by open dumping system, but increased to controlled landfill. Changes the system to reduce some environmental pollution such as air pollution and ground water pollution. The purpose of this research aims to calculate the Environmental Risk Index Mojorejo landfill. Methodology in the research used is survey, laboratory test, and evaluation method. There are three parameter criteria to get Environmental Risk Index that are assessed based on Minister of Public Works Regulation Number 03 of 2013 were landfill criteria (20 parameters), solid waste criteria at landfill (4 parameters), and leachate characteristics (3 parameters). The results showed that Mojorejo Landfill was included in the medium hazard criteria with a value of 543,36. Therefore the suggested actions are to continue the landfill sites and do rehabilitation into controlled landfill gradually. Keywords: Controlled Landfill, Environmental Risk Index, Mojorejo Landfill.